Quantification of fugitive emissions from an oil sands tailings pond by eddy covariance. (1st February 2019) - Zhang, Lucas; Cho, Sunny; Hashisho, Zaher; Brown, Casandra
Highlights: Tailings pond GHG emissions were quantified using eddy covariance technique. CH4 and CO2 fluxes showed strong daily and diurnal variability. Nighttime CH4 fluxes were higher than daytime, while nighttime CO2 fluxes were lower. Emission fluxes by eddy covariance were compared to those by flux chamber technique. Abstract: Oil sands tailings ponds are sources of greenhouse gasses (GHG) and air pollutants. The flux chamber technique, typically used to measure emissions from tailings ponds, samples a small area for a short duration, which may not account for the spatial and temporal variability of emissions from oil sands tailings ponds. The eddy covariance (EC) technique, with large spatial coverage and better temporal resolution, is a promising method to improve the accuracy of emission flux quantification. A field campaign was conducted to measure emissions from an oil sands tailings pond in Alberta using an EC system. Average CH4 and CO2 emission fluxes were 4.56 × 10 −2  g/(m 2 -d) and 3.59 g/(m 2 -d), respectively. Diurnal and daily variations of CH4 and CO2 emission fluxes were strong with relative standard deviations of 97–158%. Nighttime (18:30 to 8:00, inclusive) CH4 average emission flux (6.55 × 10 −2  g/(m 2 -d)) was 2.8 times daytime (8:30 to 18:00, inclusive) CH4 flux (2.32 × 10 −2  g/(m 2 -d)) while nighttime CO2 average emission flux (2.97 g/(m 2 -d)) was 0.7 times daytime CO2 emission flux (4.29 g/(m 2 -d)). Pearson correlation test results suggest that short-term (i.e., days to weeks) variations of CH4 and CO2 emission fluxes measured in this study were not strongly (but can be weakly) correlated with meteorological variables or the 90% cumulative flux contour distance. The CH4 and CO2 emission fluxes determined in this study were of the same order of magnitude as those from a previous study that used the EC technique at the same tailings pond. CO2 fluxes in this study were similar while CH4 fluxes in this study were more than an order of magnitude lower than fluxes based on flux chamber measurements conducted by a 3 rd party at the same location and in the same month and year. Continuous, real-time, and long-term monitoring of tailings ponds emissions is necessary to reduce uncertainty and improve representativeness and accuracy of emission flux quantification.